Investigation of Physical Quality Characteristics of Dry Land and Wet Land Wheat Varieties - Saghir Ahmed Sheikh; Benish Nawaz Merani; Aijaz Hussain Somro; Liaquat Jamali; Aasia Akbar Panhwar (Journal of Pharmacy and Nutrition Sciences, 2014)
The aim of this research study was to determine the physical characteristics of some commercial wheat varieties of dry land and wet land grown in Sindh province. Four irrigated land (Inqulab, TD-1, Kherman, and Sarsabz) wheat varieties and four drought tolerant (TK-3, Marvi, PK-85, Sassi) wheat varieties were collected from their respective areas and subjected to physical analysis. The physical characteristics of dry land and wet land wheat varieties differed significantly. It was observed that dry land wheat varieties higher in length (7.29mm) as compared to wet land wheat varieties (7.05mm). Whereas, wet land wheat varieties higher in breadth (4.97mm), thickness(3.86mm), volume (59.7mm3), geometric mean (10.66mm) and sphericity (1.72%) than those of dry land wheat varieties with breadth (4.15mm), thickness (3.25mm), volume (45.3mm3), geometric mean (9.34mm) and sphericity (1.35%). It is also observed that TKW (47g) of wet land wheat varieties were higher than those of dry land wheat varieties TKW (40.2g). Moreover, falling number (419sec) were recorded higher in wet land wheat varieties than those of dry land wheat varieties falling number (387sec). While, dry land wheat varieties increased in its hardness (55.3%) than those of wet land wheat varieties hardness (51.3%). This study reveals that availability of water and environmental factors are directly related with the nutritional characteristics of wheat varieties. This study revealed that due to more moisture content in wet land wheat varieties TKW, breadth, thickness, volume, geometric mean, falling number and sphericity were recorded as higher than dry land wheat varieties. However, Length and hardness were observed higher in dry land wheat varieties which resulted in better yield of flour as compared with wet land wheat varieties.